PENGARUH LAMA PENYIMPANAN DARAH TERHADAP JUMLAH TROMBOSIT PADA WHOLE BLOOD SEBELUM DAN SESUDAH DISIMPAN SELAMA 3 HARI DI UNITDONOR DARAH PMI KOTA MEDAN - Nelma; Roida Yuni Friski Purba (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Blood transfusion is a series of blood transfer process from a donor to a recipient. Blood is stored in the refrigerator with temperature 2-8 °c. In the blood storage process will experience changes in blood components such as platelet count. The researcher aims to determine the effect of long blood storage on platelet count on whole blood before and after being stored for three days at PMI Medan Blood Donor Unit. This research was done by descriptive method of Hematology Analyzer presented in table form. This research took place from 21-23 May 2018 at the Laboratory of Blood Transfusion Unit of Indonesian Red Cross Medan. Thenumber of samples used for the research is 10 samples. The result is the effect of storage duration on the decrease of platelet count where there is a decrease of platelet count in all donor blood samples stored for three days at PMI Medan Blood Donor Unit.Based on existing conclusions, then the suggestion that can be taken is every blood donor unit always do repeat examination for blood component level which will be transfused. For patients who will melaksanakna transfuse, you should use fresh blood. Blood should not be taken out frequently and blood refrigerator do not often open the lid. It is recommended for the same researchers in the future to increase the number of samples so that the results can be more accurate